Research on the Formation Mechanism and Mitigation Pathway of AI Cognitive Dependence in Education Context: A Cognitive Ecology Perspective - Zhang, Pan; Xiao, Yingtian (International Journal of Social Sciences and Public Administration, 2025)
The deep integration of generative artificial intelligence (AI) into the field of education expands the cognitive boundaries of subjects and improves cognitive efficiency, while potentially triggering the risk of cognitive dependence and leading to the alienation of educational values. This paper elaborates on the conceptual connotation, alienation manifestations, and potential value crisis of AI cognitive dependence in the educational context. From the perspective of cognitive ecology, a theoretical framework is constructed encompassing four dimensions-cognitive subject, technological intermediary, cognitive environment, and educational crisis-to reveal the systematic structure, dynamics, and evolutionary mechanisms of AI cognitive dependence formation. Feasible pathways to mitigate AI cognitive dependence are proposed from five aspects: technology regulation, subject empowerment, cognitive reshaping, ecological governance, and value reconstruction. Specifically, establish an ethical regulatory system for AI educational applications through data, algorithms, and scenarios; construct an effective "human-in-the-loop" mechanism and refined human-machine cognitive division of labor strategies to strengthen human cognitive dominance; restore the imbalance of cognitive structure through embodied experience enhancement and metacognitive training; implement cognitive diversity protection and ecological niche optimization strategies to maintain the resilience of the cognitive system; reaffirm the unique value of human cognition through value reconstruction and establish a cognitive perspective of "human-computer co-evolution". This paper aims to emphasize the transcendence of educational value rationality over AI instrumental rationality, realize AI’s role in promoting "cognitive enhancement rather than replacement" for subjects, construct a new cognitive ecosystem of "human-computer symbiosis", and provide early warnings and practical guidance for ethical governance in the process of educational digitalization.